Phase Evolution, Dielectric, and Electric Behavior of Sm-Doped BCTO Ceramic Fabricated by Semi-Wet Method - Prajapati D.; Rai V.S.; Kumar A.; Singh N.B.; Verma H.; Upadhyay S.; Mandal K.D. (My University, 2025)
Bi(2/3)-xSmxCu3Ti4O12 (BSCTO x = 0.05, 0.10, and 0.20) ceramics are synthesized using semi-wet technique and an extensive investigation into their structural, morphological, and elemental properties, alongside dielectric and impedance behaviors, is meticulously carried out. X-ray powder diffraction analysis unequivocally confirmed the formation of a monophasic BCTO cubic phase without any discernible secondary phases. and the crystallite size of the BSCTO ceramic, obtained by X-ray diffraction using Debye Scherrer formula, range from 62 to 81 nm. Rietveld analysis reveals that ceramics have a body centered cubic structure with space group Im-3. The Scanning electron microscope image displays the dense microstructure of the ceramics, while EDX analysis unveils the elemental composition of resulting products. Doping with Sm3+ induced a notable reduction in grain size, as observed through Scanning electron microscope and Atomic Force Microscope analyses, indicating Sm3+ hindered grain growth during sintering, potentially resulting in reduced dielectric constant (ε′). Dielectric constant and dielectric loss of the composition (x = 0.2) are found to be (Formula presented.) 152 and 0.04, respectively at room temperature (1 kHz). Impedance characteristics revealed a substantial increase in grain boundary resistance, leading to improved dielectric loss. The AC conductivity of BSCTO ceramics exhibited a frequency-dependent increase satisfying to Johncher's power law. © 2024 Wiley-VCH GmbH.